Report of the workshop of caribbean chief plant quarantine officers to discuss facilitation of caribbean intra regional trade in fresh produce - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
In this document explain two protocols were presented at the workshop: 1) that technical team should consist of one person each from the exporting and importing countries. A third independent person may be included if necessary; 2) the trading partners should decide on size of sample for produce inspection. For this reason appropriate size should precede the sample size; 3) additional researach required: - use of methyl bromide without chloropicrin, - validation of the hot water treatment technology, - CARDI to write up results of postharvest treatment trials for distribution, - and, validation of the systems approach protocol.